Nanocrystal technology, drug delivery and clinical applications - Jens-Uwe A H Junghanns Rainer H Müller (Dove Medical Press, 2008)
Jens-Uwe A H Junghanns, Rainer H MüllerDepartment of Pharmaceutical Technology, Biotechnology and Quality Management, Free University of Berlin, Berlin, GermanyAbstract: Nanotechnology will affect our lives tremendously over the next decade in very different fields, including medicine and pharmacy. Transfer of materials into the nanodimension changes their physical properties which were used in pharmaceutics to develop a new innovative formulation principle for poorly soluble drugs: the drug nanocrystals. The drug nanocrystals do not belong to the future; the first products are already on the market. The industrially relevant production technologies, pearl milling and high pressure homogenization, are reviewed. The physics behind the drug nanocrystals and changes of their physical properties are discussed. The marketed products are presented and the special physical effects of nanocrystals explained which are utilized in each market product. Examples of products in the development pipelines (clinical phases) are presented and the benefits for in vivo administration of drug nanocrystals are summarized in an overview.Keywords: drug nanocrystals, pearl milling, high pressure homogenization, nanocrystal, DissoCubes, Nanopure, bioavailability enhancement, saturation solubility, dissolution velocity